Complications of COVID-19 in Children and the Approach to the Affected Children in Pediatric Primary Care - Petr Pohunek (Pediatric Respirology and Critical Care Medicine)
Pandemics of the coronavirus SARS-Cov-2 has been circulating the world since the beginning of 2020 in several waves leaving behind many millions of affected individuals and very many fatalities. In children, the course of the disease has generally been milder that in adults; however, there was a wide range of possible serious complications observed including the pediatric fatalities. In this article, we review possible complications of COVID-19 in children and also focus on the role of pediatric primary care practitioners in the diagnosis and management of this serious disease.